Is the sleep apnoea/hypopnoea syndrome inherited?. Issue 7 (July 1993) - Douglas, N J; Luke, M; Mathur, R
Abstract : BACKGROUND--The aetiology of the sleep apnoea/hypopnoea syndrome (SAHS) is unclear in many patients. Snoring, a prerequisite for SAHS, runs in families. A study was carried out to determine whether there is an increased frequency of irregular breathing during sleep in relatives of patients with SAHS. METHODS--A prospective study was performed of first degree relatives of 20 consecutive non-obese (BMI < 30 kg/m2) patients with SAHS. Questionnaires on SAHS symptoms were sent to all first order relatives and those living within 150 miles of Edinburgh were invited for overnight monitoring of their breathing, sleep, and oxygenation patterns in the sleep laboratory. RESULTS--Ten of the 40 relatives had more than 15 apnoeas + hypopnoeas/hour of sleep, and eight had more than five 4% desaturations/hour. These frequencies of irregular breathing and desaturation are significantly higher than in the British population. Cephalometric studies showed no skeletal abnormality but an increased uvular width was found in the affected relatives. CONCLUSIONS--There is an increased frequency of abnormal breathing during sleep in relatives of non-obese patients with SAHS.